Implementasi Modul Ajar Pendidikan Agama Kristen Di SDN 1 Sabaru - Arestu Yulanda; Irma Nelyani; Selarista; Matius Herdi Ginting (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The implementation of Christian Religious Education teaching with the theme "A Forgiving Heart" based on Luke 15:11-32 has been carried out quite well and has produced positive results for students. The lesson plan (RPP) is developed in line with the Independent Curriculum and the learning objectives used in phase C, particularly in improving students’ cognitive understanding, affective attitudes, and psychomotor skills. Through various learning activities such as storytelling, group discussions, presentations, individual reflection, and the creation of Peace Hands Cards, students can more clearly understand the concept of forgiveness. Overall, students were able to remember the storyline, answered written test questions well, and demonstrated creativity in visual works. Student cooperation and participation also showed improvement, although some still needed encouragement or guidance. Observations showed that the values ​​of forgiveness were beginning to be ingrained in students through their attitudes and reflections. However, the learning process still faced several challenges such as differences in student learning abilities, a lack of self-confidence among some students, and limited time for creative activities. Overall, this learning can be said to be successful in achieving the set objectives. However, improvements are needed in terms of time management, support strategies for less active students, and a variety of learning activities to foster student courage and creativity. Therefore, these adjustments are expected to make future learning more effective, meaningful, and further instill the value of forgiveness as an essential part of Christian character.